Assessing the children’s views on foods and consumption of selected food groups : outcome from focus group approach - Sharif Ishak, Sharifah Intan Zainun; Shohaimi, Shamarina; Kandiah, Mirnalini (The Korean Nutrition Society, 2013)
The food choices in childhood have high a probability of being carried through into their adulthood life, which then contributes to the risk of many non-communicable diseases. Therefore, there is a need to gather some information about children’s views on foods which may influence their food choices for planning a related dietary intervention or programme. This paper aimed to explore the views of children on foods and the types of foods which are usually consumed by children under four food groups (snacks, fast foods, cereals and cereal products; and milk and dairy products) by using focus group discussions. A total of 33 school children aged 7-9 years old from Selangor and Kuala Lumpur participated in the focus groups. Focus groups were audio-taped, transcribed and analyzed according to the listed themes. The outcomes show that the children usually consumed snacks such as white bread with spread or as a sandwich, local cakes, fruits such as papaya, mango and watermelon, biscuits or cookies, tea, chocolate drink and instant noodles. Their choices of fast foods included pizza, burgers, French fries and fried chicken. For cereal products, they usually consumed rice, bread and ready-to-eat cereals. Finally, their choices of dairy products included milk, cheese and yogurt. The reasons for the food liking were taste, nutritional value and the characteristics of food. The outcome of this study may provide additional information on the food choices among Malaysian children, especially in urban areas with regard to the food groups which have shown to have a relationship with the risk of childhood obesity.